UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALITAS GURU DI SMK HASANUDDIN - Huda, Nur (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This type of research is descriptive qualitative, namely research that is descriptive, narrating and interpreting existing data and produces descriptive data in the form of written/spoken words from people and observable behavior and the data is in the form of statements. Data collection techniques are carried out through observation, interviews, and documentation. The data analysis technique is descriptive qualitative. Determining the validity of the data, in this study using data triangulation techniques, namely data validity checking techniques that utilize various sources outside the data as comparative material. From the results of the research and discussion, the following conclusions were obtained: The principal's efforts to improve teacher professionalism include: Involving teachers in Subject Teacher Deliberations, Involving them in training, and Attending seminars/discussions. While the teacher's efforts to improve teacher professionalism through: Subject teacher deliberations, educational training, Discussions/seminars on education. The supporting factors are: the suitability between the teacher's educational background and the field of study being taught, Community participation. And the inhibiting factors are the problem of lack of discipline, and inadequate facilities and infrastructure and the problem of funds are still needed. From the description above, the principal should be more responsible in his duties of guiding and directing teachers so that he can raise teacher awareness to further improve the quality of teaching.